FORECASTING OF ELECTRICITY CONSUMPTION OF AVIATION ENTERPRISES DURING RECONFIGURATION OF THEIR POWER SUPPLY SYSTEM - BOYKO, Sergii; SHCHOKIN, Vadim; VYSHNEVSKY, Sviatoslav; DANILIN, Olexsander; PODGORNYKH, N. (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The purpose of this work is the features of forecasting the electricity consumption of aviation companies in their introduction into the power supply system of sources of dispersed generation. At aviation enterprises, the introduction of dispersed generation power supply systems into the general structure is important. To predict, with a sufficient level of probability, the energy consumption of aviation enterprises, it is necessary to solve a multi-criteria problem. The use of neural networks in systems for forecasting energy parameters allows the use of multifactorial forecasting. This approach will improve the forecasting of generated electricity by distributed generation over time, which in turn will reduce the error of the forecast of electricity consumption from the grid in the conditions of these enterprises. The structural scheme of determination of forecast indicators of energy consumption from the network aviation enterprise, introduced into the structure of power supply of these enterprises of sources of dispersed generation, for further realization of the forecast model is offered.